Animated educational video to prepare children for MRI without sedation: evaluation of the appeal and value - Szeszak, Szofia; Man, Rachel; Love, Andrew; Langmack, Gill; Wharrad, Heather; Dineen, Robert A. (Springer, 2016)
Background: MRI scans can be distressing for children and often require sedation. Educating children about what to expect reduces anxiety and increases likelihood of successful non-sedated MRI scans. Multimedia tools are a popular means of education. Animated video could provide a free, accessible method of preparing children for MRI scans.